Comparative Determination of Vitamin C Content in Different Varieties of Tomato (Solanum lycopersicum L.) Using UV Spectrophotometry - Ainun, Nur; Daulay, Anny Sartika; Ridwanto, Ridwanto; Pulungan, Ainil Fitri (Pustaka Media Publishing, 2025)
Tomato (Solanum lycopersicum L.) is one of the most widely consumed fruits and vegetables due to its nutritional value and health benefits. This study aimed to determine the vitamin C, glucose, and crude fiber contents in different tomato varieties, namely red, yellow, green, and cherry tomatoes. The analysis included phytochemical screening, qualitative tests, and quantitative determination. Phytochemical screening was performed to identify the presence of secondary metabolites, while qualitative tests were conducted to confirm the presence of vitamin C and glucose. Quantitative analysis of vitamin C and glucose was carried out using the UV–Vis spectrophotometric method, whereas crude fiber content was determined using the gravimetric method. The results showed that flavonoids, alkaloids, and saponins were present in all tomato samples, while glycosides and tannins were detected only in certain varieties, and steroids/triterpenoids were not detected. Quantitative analysis indicated that the highest vitamin C content was found in red tomatoes (21.62 ± 0.178 µg/100 g), followed by cherry tomatoes (18.78 ± 0.002 µg/100 g), yellow tomatoes (18.38 ± 1.038 µg/100 g), and green tomatoes (12.20 ± 2.287 µg/100 g). The glucose content was 39.2 ± 0 µg/100 g in red tomatoes and 34.53 ± 0.597 µg/100 g in green tomatoes. Meanwhile, the crude fiber analysis showed the highest content in yellow tomatoes (53.44%), followed by cherry tomatoes (48.10%), red tomatoes (42.05%), and green tomatoes (40.37%). These findings indicate that different tomato varieties possess distinct nutritional profiles, and tomatoes can be considered a valuable dietary source of vitamin C, natural sugars, and dietary fiber that may contribute to maintaining human health.